Transformasi UMKM Sumatera Utara di Era Digital: Tinjauan dengan Model 7S McKinsey - Grace Elia Br Sinaga; Jonathan Kaleb Alexan Napitupulu; Sri Prakash Raj; Wina Nurfitriani; Lailan Syafrina Hasibuan (CV. ITTC INDONESIA, 2026)
MSMEs in North Sumatra face significant sustainability challenges due to market dynamics and resource limitations. This study aims to analyze the adaptation and sustainability of North Sumatran MSMEs using the McKinsey 7S Model approach. Using a qualitative-descriptive method, the research involved in-depth interviews, field observations, and document studies. The sample consisted of 40 MSME actors across Medan, Binjai, and East Kisaran selected via purposive sampling. Data was validated through triangulation and analyzed using a thematic approach based on the seven 7S elements. Findings reveal that while